Z.J. Kapera – A. Schick (red.), „When the Sun Rises Over the Earth, They Shall Bless” (4Q503). Claus-Hunno Hunzinger Memorial Volume - Tronina, Antoni (The Biblical Annals, 2022)
Book Review: Zdzisław J. Kapera – Alexander Schick (eds.) „When the Sun Rises Over the Earth , They Shall Bless” (4Q503). Professor Claus-Hunno Hunzinger Memorial Volume, The Qumran Chronicle 28–29 (2020–2021) (Kraków: The Enigma Press 2021).